Effect of cane use on bone marrow lesion volume in people with medial tibiofemoral knee osteoarthritis: randomized clinical trial. Issue 9 (September 2019) - Van Ginckel, A.; Hinman, R.S.; Wrigley, T.V.; Hunter, D.J.; Marshall, C.J.; Duryea, J.; Melo, L.; Simic, M.; Kasza, J.; Robbins, S.R.; Wallis, J.A.; Bennell, K.L.
Summary: Objective: To evaluate effects of daily cane use for 3 months on medial tibiofemoral bone marrow lesion (BML) volumes in people with medial tibiofemoral osteoarthritis (OA). Design: In this randomized controlled trial (RCT), 79 participants with medial tibiofemoral OA were randomized to either a cane group (using a cane whenever walking) or control group (not using any gait aid) for 3 months. The cane group received a single training session by a physiotherapist, using a biofeedback cane to teach optimal technique and body weight support and motor learning principles to facilitate retention of learning. The primary outcome was change in total medial tibiofemoral BML volume (per unit bone volume) measured from magnetic resonance imaging (MRI) at 3 months. Secondary outcomes were BML volumes (per unit bone volume) of the medial tibia and femur, and patient-reported outcomes of overall knee pain, knee pain on walking, physical function, perceived global symptom changes and health-related quality of life. MRI analyses were performed by a blinded assessor. Results: Seventy-eight participants (99%) completed the primary outcome. Mean (standard deviation) daily cane use was 2.3 (1.7) hours over 3 months. No evidence of between-group differences was found for change in total medial tibiofemoral BML volume (mean difference: −0.0010 (95% confidence intervals: −0.0022, 0.0003)). Most secondary outcomes showed minimal differences between groups. Conclusion: Daily use of a cane during walking for 3 months aiming to reduce knee joint loading did not change medial tibiofemoral BML volumes compared to no use of gait aids. Clinical trial registration: Australian New Zealand Clinical Trial Registry (ACTRN12614000909628).